Poly(ADP-Ribosyl)ation - Bürkle, Alexander (Molecular Biology Intelligence Unit, 2006)
Poly(ADP-Ribosyl)ation comprises 19 chapters written by leading international experts in the field and is richly illustrated. Extensive bibliography is given in each chapter.